Development of Powtoon-Based Audio-Visual Media in Chemical Bonding Materials - Delila Sembiring; Nora Susanti (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2023)
This research was conducted at Medan 11 Public High School with the background being that the teacher had never developed audio-visual media on chemical bonding material with a variety of learning media. This study aims to find out how the needs of teachers and students for learning media, determine the feasibility of media developed on chemical bonding material and to find out how students respond to this development. The type of research used is research and development (R&D) using the 4D model (Define, Design, Development, Disseminate). The data that has been obtained through the questionnaire instrument for the needs of teachers and students is analyzed using the proportion formula and then described. Based on the validation results of the animated video learning media that had been developed by 22 validator teams, an overall average score was obtained with a total proportion of 90.04% with the qualification "very feasible". The results of the trial on students through the distribution of response questionnaires obtained a score with a total proportion of 90.63% with the qualification "strongly agree". Overall, it can be interpreted that the development of powtoon-based audio-visual media on chemical bonding materials has been categorized properly.